2019
DOI: 10.36380/jwpr.2019.23
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Dietary Addition of Palm and Coconut Oils in Steaming Tomato (Lycopersicon esculentum) Waste Powder on Digestibility of Crude Fiber and Retention of Lycopene and Nitrogen in Broiler Chickens.

Abstract: Lycopene is a powerful antioxidant present in tomatoes and other vegetables and fruits. Present research was carried out to evaluate lycopene and nitrogen retention and crude fiber (CF) digestibility of steaming tomatoes waste powder which was combined with oil. Tomatoes waste in this experiment were local fresh tomato rejected from tomato field around West Sumatera province, Indonesia. The experimental factors were included the type of oil (palm and coconut oils) and dosage of oils (0.25, 0.5, 0.75, 1, and 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This is presumably due to differences in the digestibility of commercial lycopene and lycopene derived from PTW. Handayani et al (2019) it was found that the retention of lycopene in tomato waste with adding coconut oil was only around 61.74%. This study showed the same results with the report of Mahata et al (2016) that the administration of 12% tomato flour which had been processed by boiling for 8 minutes could reduce blood serum cholesterol of laying hens.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…This is presumably due to differences in the digestibility of commercial lycopene and lycopene derived from PTW. Handayani et al (2019) it was found that the retention of lycopene in tomato waste with adding coconut oil was only around 61.74%. This study showed the same results with the report of Mahata et al (2016) that the administration of 12% tomato flour which had been processed by boiling for 8 minutes could reduce blood serum cholesterol of laying hens.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, lycopene is hydrophobic and lipophilic so that its absorption in the gastrointestinal tract is influenced by the presence of lipids (Colle et al, 2012;Trujillo and Mc-Clements, 2016). Therefore, according to Handayani et al (2018Handayani et al ( , 2019 the rejected tomatoes were first treated with heat, namely steaming at 98°C for 12 minutes and then adding 0.5% coconut oil. It aims to release lycopene from the tomato skin matrix, change its structure in the form of trans lycopene into the form of cis lycopene and increase the absorption of lycopene in the digestive tract in laying hens.…”
Section: Advances Inmentioning
confidence: 99%
See 1 more Smart Citation